1995
DOI: 10.1515/znb-1995-0318
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Catalyzed Alternating Cooligomerization of Ethylene and Carbon Monoxide to Unsaturated Ketones

Abstract: Cationic palladium catalysts have been used to cooligomerize ethylene and carbon monoxide. At high ethylene/CO ratios (m /m = 10:1) in methylene chloride as a solvent, unsaturated alternating cooligomers of the general structure R[C(O)CH2CH2]mH ( m ≥ 1 ; R ≡CH2=CH-, CH2=CHCH2CH2- and CH3CH = CHCH2-) were obtained for the first time. Single component catalyst precursors [(allyl)Pd(P^X )]+Y- (P^X = Ph2P(CH2)nC(= O )OR, Ph2P(CH2)2P(=O)Ph2, Ph2P(CH2)nPh2P(CH2)2S (=O )Ph, n = 1 - 3 , R = Me, Et; Y- = BF4-, SbF6- ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 0 publications
1
30
0
1
Order By: Relevance
“…Endowed with soft and hard donor groups, phosphorus–oxygen and phosphorus–nitrogen based ligands represent the most studied class of functional phosphanes and many such examples have been presented in the previous section. The oxygen functional groups associated with the phosphorus donor come from alcohol, ether, ketone, ester, amide, and phosphane oxide or phosphonate groups 1, 2, 26, 27, 43, 78, 90–94. Although these various functions will impart significant changes in the coordination properties and hemilability of the corresponding P,O ligands, it is generally observed that phosphorus–oxygen ligands are the most weakly chelating type of ligand.…”
Section: Hemilabile Ligandsmentioning
confidence: 99%
“…Endowed with soft and hard donor groups, phosphorus–oxygen and phosphorus–nitrogen based ligands represent the most studied class of functional phosphanes and many such examples have been presented in the previous section. The oxygen functional groups associated with the phosphorus donor come from alcohol, ether, ketone, ester, amide, and phosphane oxide or phosphonate groups 1, 2, 26, 27, 43, 78, 90–94. Although these various functions will impart significant changes in the coordination properties and hemilability of the corresponding P,O ligands, it is generally observed that phosphorus–oxygen ligands are the most weakly chelating type of ligand.…”
Section: Hemilabile Ligandsmentioning
confidence: 99%
“…Figs. 2 and 6 display the different arrangements of oxygens in free L and in the complexes, being on the opposite sides of an ideal plane C(1 I), C(12), C(5), C (6) in the former and on the same side in the complexes. Although this comparison shows the great flexibility of the ligand, the coordination to Pd might induce a strain in the propane-and butane-dioloxy bridges, as appears from the increased bond angles at oxygens (up to 123"), compared with the value observed i n free L2 (Table 6).…”
Section: Synthesis and Characterisation Of Complexes 1 Andmentioning
confidence: 99%
“…[1,2,3] Their interest in catalysis arises from the easy decoordination of the weak donor centre without the displacement of the ligand, which should confer a better stability to the reaction intermediates. Mixed ligands containing phosphorus along with oxygen, nitrogen or sulphur donor atoms have specifically been designed for use in catalytic reactions such as hydrogenation, [4,5,6] oligomerisation, [7] and hydroformylation of olefins. [8] Pyrazole-derived molecules are good candidates for the preparation of interesting N,NЈ or N,P mixed ligands, owing to their ease of synthesis and the possibility of electronic and steric modulation of their properties.…”
Section: Introductionmentioning
confidence: 99%